Effects of fine-grinding corn or dried distillers grains with solubles and diet form on growth performance and caloric efficiency of 25- to 50-lb nursery pigs - Jon A De Jong; Joel M DeRouchey; Michael D Tokach; Robert D Goodband; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2013)
A total of 687 pigs (PIC 1050 barrows; initially 25.5 lb BW and 37 d of age) were used in a 21-d study to determine the effects of fine-grinding corn or dried distillers grains with solubles (DDGS) and diet form on nursery pig performance and caloric efficiency. Pens of pigs were balanced by initial BW and randomly allotted to 1 of 10 dietary treatments with 14 replications per treatment. There were 5 pigs per pen in two groups of nursery pigs. The 10 experimental diets included 4 corn-soybean meal—based diets consisting of: (1) corn ground to 638 Î¼, in meal form; (2) treatment 1 in pellet form; (3) corn ground to 325 Î¼, in meal form, and (4) treatment 3 in pellet form. The remaining 6 diets contained 30% DDGS. Diets 5 through 10 consisted of: (5) corn and DDGS ground to 638 and 580 Î¼, in meal form; (6) diet 5 in pellet form; (7) corn and DDGS ground to 638 and 391 Î¼, in meal form; (8) diet 7 in pellet form; (9) corn and DDGS ground to 325 and 391 Î¼, in meal form; and (10) diet 9 in pellet form. Overall (d 0 to 21), a corn particle size (regardless of DDGS addition) × diet form interaction was observed (P<0.01) as a result of increased ADFI when corn was finely ground and fed in pellet form but decreased intake when corn was finely ground and fed in meal form. Pelleting diets decreased (P<0.001) ADG, ADFI, and final BW but improved (P<0.001) F/G and caloric efficiency on both an ME and NE basis. Finegrinding corn decreased (P<0.04) ADG as a result of numerically decreased ADFI (P<0.16). Feeding 30% DDGS also decreased (P<0.01) ADG, ADFI, and NE caloric efficiency and tended to decrease (P<0.07) final BW. In conclusion, pelleting diets and fine-grinding ingredients reduced ADG as a result of decreased ADFI, but pelleting improved feed efficiency. Feeding 30% DDGS was detrimental to nursery pig growth performance.; Swine Day, Manhattan, KS, November 21, 2013
Keywords: Swine day; 2013; Kansas Agricultural Experiment Station contribution; no. 14-044-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1092; DDGS; Nursery pig; Particle size; Pelleting